Kecerdasan Kinestetik menurut Gardner: Strategi Penguatan Motorik Halus Usia 5–6 Tahun untuk Kesiapan Pendidikan Lanjutan - Nadelia Balqis; Khairunnisa Azzahra; Ulwan Syafrudin (Early Childhood Journal, 2026)
Kinesthetic intelligence, as proposed by Howard Gardner, is a key pillar in the development of children aged 5–6 years, particularly in strengthening fine motor skills as a prerequisite for school readiness, yet applied interventions remain largely conventional. This study aims to synthesize effective kinesthetic-based strategies through a Systematic Literature Review (SLR) following PRISMA guidelines, searching the Google Scholar and Portal Garuda databases. From 87 initial articles, 10 primary articles were included in the final synthesis and analyzed through content analysis. The findings identify three main strategy clusters, namely manipulative activities (busy book), explorative techniques (ecoprint), and tactile stimulation (magic sand), which significantly improve finger dexterity and hand-eye coordination compared to conventional methods. These findings affirm the importance of integrating Gardner's kinesthetic principles into early childhood curricula to support a smoother transition to primary education.